Youth for Peace Camp - Yusuf, Yusuf; Zabidi, Nouvel (Proceedings of Annual Conference for Muslim Scholars, 2024)
The aim of this research is to understand the role of Islamic philanthropic institutions in channelling funds through youth community empowerment programs to foster a sense of harmony and tolerance, as well as the relationship between professionalism and the enhancement of Islamic values. This research employs a descriptive qualitative method, combining literature research and case studies on the philanthropic institution Dompet Duafa. The results indicate the role of Dompet Duafa in realising programs that enhance harmonious and tolerant attitudes, as well as a positive relationship between professionalism and the promotion of Islamic values. This study focusses on youth community empowerment programs in specific regions and religions that can lead to the generalisation of findings. Future studies are expected to expand the participant community. The implications of this study offer valuable insights for philanthropic institutions and government policymakers in designing empowerment programs and initiatives. This research contributes to emphasising the role of professionalism and optimisation as catalysts for enhancing Islamic values through local wisdom in maintaining harmonious and tolerant attitudes among youth.